Thermal and Acoustic Design of a Shelter for High-Voltage Electrical Equipment - Somayan Basu; Edoardo Piana (Applied Sciences)
The growing demand for electric energy requires smarter and quicker distribution systems. In urban contexts, a smarter distribution of electric power to various classes of consumers, according to their demands, is possible through compact sorters. Since this type of device must be protected from unwanted access by people, wildlife and inclement weather, protection must be placed around the main components. When deployed in urban areas, housing can be built using solid panels. However, there is a risk of overheating the vital and costly parts of the system with the possibility to cause malfunction and, in extreme cases, damage. Moreover, leaving the system open exposes nearby residents to the impulsive noise produced during the operation of the switchgears being part of the system. Hence, there is a need to reach a suitable trade-off between optimal heat transfer and noise propagation. This article attempts to explain the thermal design backed by experimental validation and the noise-spreading modelling necessary to assess the respect of environmental legislation.